Estratégias de cultivo de células-tronco derivadas do tecido adiposo humano para promover a regeneração tecidual óssea in vivo - Ana Claudia Chagas de Paula (2015)
Large cranial defects do not regenerate successfully, posing an important biomedical issue. The current approaches to heal the bone tissue still face some limitations and thus, the tissue engineering is an attractive science to bypass these limitations. Human adipose-derived stem cells (hASCs) are currently a point of focus for tissue engineering applications. Prior to their clinical application, hASCs must be expanded ex vivo to obtain the required number of cells for transplantation. However, the ex vivo expansion of stem cells before clinical application remains a challenge. The fetal bovine serum (FBS) is largely used as a medium supplement and exposes the recipient patient to infections and immunological reactions after tranplantation. Furthermore, the cell expansion poses a risk of malignant cell transformation. Therefore, the aim of this study was to evaluate if the hASCs are resistant to spontaneous transformation during expansion in a xeno-free culture condition, using a pooled allogeneic human serum (HS) as well as the capacity of hASCs cutured in poly-hydroxybutyrate-co-3-hydroxyvalerate (PHB-HV) scaffolds to differentiate in osteogenic lineages and to heal critical-size calvarial defect in imunodeficient mouse. The hASCs expanded in medium supplemented with HS did not show remarkable differences in morphology, viability, differentiation capacity and immunophenotype. The main difference observed was a significantly higher proliferative effect on hASCs cultured in HS compared to FBS. There was no significant difference in C-FOS expression, but C-MYC protein expression was enhanced in HS cultures compared to FBS cultures. However no difference was observed in MYC, CDKN2A, ERBB2 and TERT mRNA levels. Moreover, the hASCs presented normal karyotype undergoing senescence, and did not form in vivo tumors, eliminating the possibility of spontaneous immortalization of hASCs in the presence of HS. The PHB-HV scaffolds developed by the freeze-drying technique showed an adequate porous structure and mechanical performance suitable for allowing cell colonization. The scaffolds were not toxic to cells as shown by MTT assay. And the osteogenic differentiation of hASCs cultured on scaffolds was confirmed by the reduction of the proliferation, the alkaline phosphatase activity, gene expression of ALPL, COL1A1, RUNX2 and BGLAP, and the expression of bone markers, such as collagen type I, osteopontin and osteocalcin. Furthermore, the PHB-HV scaffold demonstrates high degree of biocompatibility in vivo. In the last step of this thesis, although the histological analysis showed a good progression of the bone injury with neoangiogenesis, the implanted PHB-HV scaffolds seeded with/without hASCs were not able to heal critical-size mouse calvarial defects after 12 weeks of implantation. Overall, the findings suggest that the HS is an approach suitable and safe to culture hASCs and differentiate these cells in osteogenic lineages intended for clinical applications. And the PHB-HV scaffold seems to be adequate for cell growth and differentiation of hASCs usefull for bone tissue engineering, but further studies are needed.